2007
DOI: 10.1073/pnas.0611454104
|View full text |Cite
|
Sign up to set email alerts
|

Following evolution's lead to a single residue switch for diterpene synthase product outcome

Abstract: There have been few insights into the biochemical origins of natural product biosynthesis from primary metabolism. Of particular interest are terpene synthases, which often mediate the committed step in particular biosynthetic pathways so that alteration of their product outcome is a key step in the derivation of novel natural products. These enzymes also catalyze complex reactions of significant mechanistic interest. Following an evolutionary lead from two recently diverged, functionally distinct diterpene sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
164
0
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 164 publications
(181 citation statements)
references
References 22 publications
14
164
0
3
Order By: Relevance
“…In previous work, we found that a specific single residue change (Ile to Thr) was sufficient to "short circuit" the complex cyclization reaction catalyzed by ent-kaurene synthases to instead produce ent-pimara- 8(14),15-diene, presumably by deprotonation of a mechanistically relevant ent-pimar-15-en-8-yl + intermediate. 5 Here we demonstrate that AgAS product output can be switched from abietadienes to pimaradienes by a similar single residue change, albeit with subtle differences that have important mechanistic implications.…”
mentioning
confidence: 67%
See 2 more Smart Citations
“…In previous work, we found that a specific single residue change (Ile to Thr) was sufficient to "short circuit" the complex cyclization reaction catalyzed by ent-kaurene synthases to instead produce ent-pimara- 8(14),15-diene, presumably by deprotonation of a mechanistically relevant ent-pimar-15-en-8-yl + intermediate. 5 Here we demonstrate that AgAS product output can be switched from abietadienes to pimaradienes by a similar single residue change, albeit with subtle differences that have important mechanistic implications.…”
mentioning
confidence: 67%
“…5 Alignment of these conifer diterpene cyclases with those from rice (Oryza satiVa) utilized in our previous study revealed that there was only a small change in aliphatic side chain size at the corresponding position. In particular, AgAS and PaAS contain a Val at this position, while PaPS has a Leu ( Figure 1).…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…11 An alternative path to the atiserane diterpenes would involve ring opening of a free or enzyme-bound trachylobane intermediate.…”
Section: Supporting Information Availablementioning
confidence: 99%
“…Kinetic runs were conducted at 10 nM protein concentration according to recently published procedures. 11 Reactions were initiated by addition of [15-3 H]ent-copalyl PP (5), 14e and [14-3 H]ent-kaurene was isolated by extraction and analyzed by liquid scintillation counting. 11,43 (Table 3) Studies with native KS partially purified from wild cucumber (Marah macrocarpus) seeds demonstrated that ring rearrangement occurs during the enzyme catalyzed cyclization of entcopalyl PP.…”
Section: Inhibition Of Ent-kaurene Synthasementioning
confidence: 99%